NILAI PENDIDIKAN RELIGIUS DALAM PERAYAAN HARI RAYA NYEPI - Abdullah Muslich Rizal Maulana; Vina Lathifatun Nafsiyah; Darlisa Pritama, Wa Ode Sitti; Yesi Ameilia Pramesti (Guna Widya: Jurnal Pendidikan Hindu, 2024)
One of the major Hindu holidays in Indonesia is Nyepi day, where the holiday is held or commemorated to welcome the arrival of Saka day. Meanwhile, according to its dating, the Saka new year falls on the Apisan Sasih Kedasa or Eka Sukla Paksa Waisaka calendar, which is exactly the day after Tilem Kesanga or Panca Dasi Krisna Paksa Sasih Chaitra. The commemoration of Nyepi day itself has meaning in every series that was carried out before. Some of the ceremonies or rituals that are carried out are the Melasti Ceremony and also Tawur Kesanga. The Melasti ceremony itself aims to eliminate the suffering of the people, releasing the impurity and filthiness of the people, which is explained in the lontar Sanghyang Aji Swandala. Meanwhile, in the Sundarigma lontar, it is explained that the Tilem day of the month of Chaitra is the day of purification of the Gods, taking the water of life in the middle of the ocean, therefore Hindu people/men should observe and make offerings to the Gods. Nyepi day is the best day to make oneself a better person than before and as an effort to establish a true self. It is at the time of Nyepi that Hindus can continue to remember the essence of truth because only truth is eternal among others. Keywords: Nyepi, Hinduism, Spiritual, Saka